Erythropoiesis from Human Embryonic Stem Cells Through Erythropoietin-Independent AKT Signaling. (23rd May 2014) - Kim, William S.; Zhu, Yuhua; Deng, Qiming; Chin, Chee Jia; He, Chong Bin; Grieco, Amanda J.; Dravid, Gautam G.; Parekh, Chintan; Hollis, Roger P.; Lane, Timothy F.; Bouhassira, Eric E.; Kohn, Donald B.; et al.
Abstract: Unlimited self renewal capacity and differentiation potential make human pluripotent stem cells (PSC) a promising source for the ex vivo manufacture of red blood cells (RBCs) for safe transfusion. Current methods to induce erythropoiesis from PSC suffer from low yields of RBCs, most of which are immature and contain embryonic and fetal rather than adult hemoglobins. We have previously shown that homodimerization of the intracellular component of MPL (ic-MPL) induces erythropoiesis from human cord blood progenitors. The goal of this study was to investigate the potential of ic-MPL dimerization to induce erythropoiesis from human embryonic stem cells (hESCs) and to identify the signaling pathways activated by this strategy. We present here the evidence that ic-MPL dimerization induces erythropoietin (EPO)-independent erythroid differentiation from hESC by inducing the generation of erythroid progenitors and by promoting more efficient erythroid maturation with increased RBC enucleation as well as increased gamma:epsilon globin ratio and production of beta-globin protein. ic-MPL dimerization is significantly more potent than EPO in inducing erythropoiesis, and its effect is additive to EPO. Signaling studies show that dimerization of ic-MPL, unlike stimulation of the wild type MPL receptor, activates AKT in the absence of JAK2/STAT5 signaling. AKT activation upregulates GATA-1 and FOXO3 transcriptional pathways with resulting inhibition of apoptosis, modulation of cell cycle, and enhanced maturation of erythroid cells. These findings open up potential new targets for the generation of therapeutically relevant RBC products from hPSC. Stem Cells   2014;32:1503–1514